2002
DOI: 10.1128/jb.184.22.6198-6206.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Changes on Expression of the Oligopeptide Permease ( opp ) Genes of Borrelia burgdorferi

Abstract: We analyzed expression of a putative oligopeptide permease (Opp) of Borrelia burgdorferi. Unlike the opp operons of other bacteria for which there is a single substrate binding protein, B. burgdorferi codes for three substrate binding proteins (OppA-I to -III) in its opp operon and an additional two homologs on plasmids (OppA-IV and -V). Instead of a single promoter region regulating transcription of the entire operon, as seen in other bacterial opp operons, it appears that among oppA-I, -II, and -III, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
82
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 19 publications
3
82
0
Order By: Relevance
“…Moreover, B. burgdorferi has limited metabolic capabilities with (i) few ORFs annotated as regulators of gene expression; (ii) no apparent biosynthetic pathways for synthesis of various amino acids, fatty acids, and nucleotides; and (iii) limited transport systems for acquiring key nutrients from the external environment. We therefore decided to investigate the role of one of the five paralogs of oligopeptide permease A proteins, BBA34, in vertebrate host-specific adaptation since it is (i) preferentially upregulated upon propagation of B. burgdorferi under conditions mimicking the mammalian host, (ii) incapable of binding oligopeptides, (iii) immunogenic, and (iv) comprised of a solute binding domain capable of binding/transporting key solutes (85). We undertook a genetic approach to assess the contribution of this lp54-encoded protein to vertebrate host-specific conditions by deleting bba34 in a noninfectious lp25-deficient strain ML23 (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, B. burgdorferi has limited metabolic capabilities with (i) few ORFs annotated as regulators of gene expression; (ii) no apparent biosynthetic pathways for synthesis of various amino acids, fatty acids, and nucleotides; and (iii) limited transport systems for acquiring key nutrients from the external environment. We therefore decided to investigate the role of one of the five paralogs of oligopeptide permease A proteins, BBA34, in vertebrate host-specific adaptation since it is (i) preferentially upregulated upon propagation of B. burgdorferi under conditions mimicking the mammalian host, (ii) incapable of binding oligopeptides, (iii) immunogenic, and (iv) comprised of a solute binding domain capable of binding/transporting key solutes (85). We undertook a genetic approach to assess the contribution of this lp54-encoded protein to vertebrate host-specific conditions by deleting bba34 in a noninfectious lp25-deficient strain ML23 (Fig.…”
Section: Figmentioning
confidence: 99%
“…However, unlike other bacteria, B. burgdorferi has 5 open reading frames (ORFs) annotated as homologs of OppA, suggesting that these proteins could play a significant role in acquiring select nutrients/solutes in specific microenvironments (11). Three of these OppA homologs (OppA1, -2, and -3) encoded on the chromosome bound heptapeptides with high affinities in a pH-dependent manner, while the other two homologs present on plasmids (OppA4 on cp26 and OppA5 or BBA34 on lp54) did not exhibit such binding characteristics (84,85). Additional studies also indicated that bba34 was upregulated when the culture conditions of B. burgdorferi were shifted from 25°C to 37°C and in spirochetes present in infected mouse tissues (52).…”
mentioning
confidence: 99%
“…B. burgdorferi undergoes a complex natural life cycle in which it encounters vast changes in environmental conditions, such as nutrient availability, temperature, and pH, as it moves from tick to mammalian hosts. The individual promoters have been shown to respond differentially to various environmental conditions (29). For example, the expression of OppA-4 and OppA-5 is highly up-regulated by the bacteria in a mouse host, while the expression of OppA-1 is relatively constitutive regardless of whether the bacteria are grown in vitro or are present in tick or mouse hosts.…”
mentioning
confidence: 99%
“…Wang et al found that each of the five B. burgdorferi OppA orthologues is under the control of a separate promoterwhich would allow for individual regulation of the expression of the proteins (29). B. burgdorferi undergoes a complex natural life cycle in which it encounters vast changes in environmental conditions, such as nutrient availability, temperature, and pH, as it moves from tick to mammalian hosts.…”
mentioning
confidence: 99%
“…Not unexpectedly, the entry of a bloodmeal into a B. burgdorferi-infected tick is accompanied by extensive changes in the borrelial transcriptome and proteome, a process referred to as mammalian host adaptation (1,4,43). While a number of studies have demonstrated that the expression of many borrelial loci can be modulated by the manipulation of in vitro growth conditions (1,2,5,8,10,11,17,27,32,41,48,51,58,60,(63)(64)(65)68), we and others have shown that as-yet-undefined mammalian hostspecific cues are essential for triggering the genetic program(s) underlying host adaptation (1,2,8,18,27,32,46,49,51,52,63,64,66).…”
mentioning
confidence: 99%